(untitled) (Swiss Medical Weekly, 2015)
The vast majority of tumours are characterised by high frequencies of genetic and epigenetic alterations resulting in tumour-specific antigens, which may, in principle, be recognised by cytotoxic T cells. Though early clinical immunotherapy trials have yielded mixed results with ambiguous clinical benefit, cancer immunotherapy is now attracting increasing attention as a viable therapeutic option, mainly in melanoma and lung cancer, but increasingly also in other malignancies. In particular, recent therapeutic efforts targeting inhibitory receptors on T cells to overcome tumour-induced immune dysfunction have the potential to reshape current treatment standards in oncology. The clinical development has been pioneered by the antibody ipilimumab, which blocks cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) and has demonstrated survival benefit in two randomised landmark trials in melanoma. Capitalising on this success, the research on the clinical implication of T cell checkpoint inhibition has been boosted. Early clinical trials have demonstrated meaningful response rates, sustained clinical benefits with encouraging survival rates and good tolerability of next-generation checkpoint inhibitors, including programmed death-1 (PD-1) and programmed death ligand 1 (PD-L1) inhibitors, across multiple cancer types. Attractive perspectives include the concurrent blockade of immunological (non-redundant) checkpoints, which has recently been demonstrated using combinations of immune checkpoint modulators themselves or with other therapies, such as chemotherapy, targeted therapy or radiotherapy. This article summarises the mechanism of action and subsequent clinical studies of immune checkpoint antibodies in oncology with a particular focus on melanoma and lung cancer.